POTRET GURU SEKOLAH DASAR DALAM MENGELOLA PEMBELAJARAN - , Fakhruddin (Pendidikan Dasar, 2009)
Abstract: The present research aims to describe teachers’ ability of instructional management. Sample of this study are Primary School Teachers of Kota Semarang, Central Java. For the purpose of the study, data was collected through documentation and observation techniques. The findings indicate that; (1) of the instructional plans designed by the teachers observed 33.9% were adequately developed yet still 6.9% of them were not quite well developed; (2) of the teachers’ instructional performance observed 29.9% could be categorized well-run, whilst 9.2% of them were not quite well; (3) seen from the lens of their ability to evaluate learning outcomes, 45.4% teachers could be categorized as strongly capable, whilst 6.9% teachers were not quite capable. Based on these findings, in order to manage their instruction more effectively, it is highly recommended for the teachers to; (1) understand comprehensively their pupils; (2) master the subject matter deeply; (3) as a part of their accountabilities to the stakeholders, the teachers need to develop their evaluation report more systematically, effectively as well as transparently.